The Difference Expressions of EBNA-1 in Epstein-Barr Virus Infection in Low and High Grade Colorectal Carcinoma - Epistel Pangujian Simatupang; Marcellus Simadibrata; Rino Alvani Gani; Dyah Ratna Budiani (The Indonesian Society for Digestive Endoscopy, 2012)
Background: Colorectal carcinoma is a common malignancy with the highest mortality rate. Epstein- Barr virus (EBV) as the virus that most commonly infect humans, also can infect the body in a latent and induce the occurrence of malignancy. This study aimed to prove an association between EBV virus infection with degree of colorectal carcinoma by examining the main EBV oncogene expression, namely Epstein-Barr nuclear antigen-1 (EBNA-1), in low grade and high grade colorectal carcinoma. Method: Cross-sectional study was performed in 14 colorectal cancer patients in Moewardi Hospital, Surakarta between July 2011 and January 2012. The biopsy specimens were stained for EBNA-1 expression using immunohistochemical technique. Statistical analysis was performed using T-test and Mann-Whitney by SPSS software version 19.0 for windows. Results: Of the 14 patients, there were 7 patients with low grade colorectal carcinoma and 7 patients with high grade colorectal carcinoma. EBNA-1 expression was found in epithelium of low grade and high grade colorectal carcinoma with p = 0.01; CI = -5.24-0.88. We also assessed the expression of EBNA-1 on lymphocytes B of low grade colorectal carcinoma and high grade colorectal carcinoma with p = 0.043. Conclusion: Significant differences in the expression of EBNA-1 was found in association with EBV infection either in low grade and high grade colorectal carcinoma. The role of EBNA-1 as tumor initiator needs to be elucidated further. Keywords: carcinoma colorectal, Epstein-Barr virus, EBNA-1